Relatório de Estágio Profissional "Aprender a Ser Professor: Um Processo de Reflexão Continua" - Vasco Filipe Abreu Barbosa (2018)
The elaboration of this document, Practicum Report, configured a great importance,since it allowed me to report, supported by renowned authors, all thatwas experienced throughout this school year (2009/2010), a long journey oftraining as pre-service Physical Education teacher. The Supervised Teachingheld at the Oliveira do Douro middle school, and it was monitored by the CooperatingTeacher and the Supervisor belonging to the Faculdade de Desportoda Universidade do Porto. The structure of this document is divided into fourchapters: introduction - mention of what will be treated; personal dimension - ispictured my life journey, my understanding about the internship and my initialexpectations; framework of professional practice - is characterized the school,the environment, the material conditions and the students were I realized mypracticum; achievement of professional practice - subdivided in three performanceareas (Area 1 - "Organization and Management of Teaching and Learning"; Area 2 - "Participation in School and Relations with the Community ";Area 3 - "Professional Development"); Final considerations - which includes theconclusions of the internship and future perspectives.